The atmospheric oxidizing capacity in China – Part 1: Roles of different photochemical processes - J. Dai; G. P. Brasseur; G. P. Brasseur; G. P. Brasseur; M. Vrekoussis; M. Vrekoussis; M. Vrekoussis; M. Kanakidou; M. Kanakidou; K. Qu; Y. Zhang; H. Zhang; et al. (Atmospheric Chemistry and Physics, 2023)
Atmospheric oxidation capacity (AOC) characterizes the ability of the atmosphere to scavenge air pollutants. However, the processes involved in China, where anthropogenic emissions have changed dramatically in the past decade, are not fully understood. A detailed analysis of different parameters that determine the AOC in China is presented on the basis of numerical simulations performed with the regional chemical–meteorological Weather Research and Forecasting model with Chemistry (WRF-Chem). The model shows that the aerosol effects related to extinction and heterogeneous processes produce a decrease in surface ozone of approximately 8–10 ppbv in NOx-limited rural areas and an increase of 5–10 ppbv in VOC-limited urban areas. In this latter case, the ozone increase is noticeable for aerosol concentrations ranging from 20 to 45 µg m−3 in July 2018. The ozone reduction in NOx-sensitive regions is due to the combined effect of nitrogen dioxide and peroxy radical uptake on particles and of the light extinction by aerosols, which affects the photodissociation rates. The ozone increase in VOC-sensitive areas is attributed to the uptake of NO2 by aerosols, which is offset by the reduced ozone formation associated with HO2 uptake and with aerosol extinction. Our study concludes that more than 90 % of the daytime AOC is due to the reaction of the hydroxyl radical with VOCs and carbon monoxide. In urban areas, during summertime, the main contributions to daytime AOC are the reactions of OH with alkene (30 %–50 %), oxidized volatile organic compounds (OVOCs) (33 %–45 %), and carbon monoxide (20 %–45 %). In rural areas, the largest contribution results from the reaction of OH with alkenes (60 %). Nocturnal AOC is dominantly attributed to the reactions with the nitrate radical (50 %–70 %). Our results shed light on the contribution of aerosol-related NOx loss and the high reactivity of alkenes for photochemical pollution. With the reduction in aerosols and anthropogenic ozone precursors, the chemistry of nitrogen and temperature-sensitive VOCs will become increasingly important. More attention needs to be paid to the role of photodegradable OVOCs and nocturnal oxidants in the formation of secondary pollutants.